PENGARUH PENDAPATAN USAHA, BIAYA OPERASIONAL DAN BIAYA PRODUKSI TERHADAP LABA BERSIH PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2019-2023 TRIWULAN 1-4 - Kusnadi, Kusnadi; Luthfi, Muhammad; Hildayani, Maida (Jurnal Ilmiah Akuntansi Rahmaniyah, 2025)
The food and beverage sub-sector plays a crucial role in advancing Indonesia’s processing industry and contributes significantly to the national economy. This study analyzes the influence of business income, operational expenses, and production costs on the profitability of food and beverage companies listed on the IDX from 2019 to 2023. Based on 80 samples and SPSS 26 analysis, the findings reveal that all three variables positively and significantly affect profits, both individually and simultaneously.